A lightweight secure architecture for wireless sensor networks. (8th February 2010) - Collins, Michael; Dobson, Simon; Nixon, Paddy
The adoption and widespread deployment of wireless sensor networks means that security issues are of critical concern. To date, much research has focused on the usability of these networks in a variety of environments where conventional wired networks may not be feasible. However, less emphasis was placed on the security issues of employing a sensor network and its exposure to potential threats. Due to the severe physical constraints in sensor nodes, traditional cryptographic mechanisms are not suitable to deal with such potential security threats. This paper proposes a secure lightweight architecture that takes account of the constraints of sensor networks. With the use of a base station, a hierarchical network topology is formed that enables end-to-end communication between sensor nodes with the aid of intermediary nodes where necessary. The architecture also supports the detection and isolation of aberrant nodes.